Faktor-Faktor yang Berhubungan dengan Persepsi Masyarakat Urban Terhadap Program Vaksinasi Nasional COVID-19 di Kota Sumbawa Besar Provinsi NTB - Fachry Prasetyo Hutomo (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Since 2020, vaccination has been running to overcome the COVID-19 pandemic, NTB. The vaccination program is still at a stagnant pace. The pace of vaccination can be influenced by several factors, especially public perception of vaccination. This research was conducted in two villages of Sumbawa Besar Regency in the period October-November 2020. The research was carried out using research instruments in the form of questionnaires. The sample collection technique used SLOVIN and obtained 100 respondents. This study used a cross-sectional method with data testing using the Chi-square statistical test and Fischer's Exact Test. The results of this study showed that most respondents had a good perception of COVID-19 vaccination and the absence of a meaningful relationship between age (p=0.746), gender (p=0.923), degree of education (p=0.837), and level of knowledge (p=0.064) with the level of respondents' perception of the national COVID-19 vaccination program.